Covalent functionalization of molybdenum disulfide by chemically activated diazonium salts. Issue 5 (28th January 2021) - Daukiya, Lakshya; Teyssandier, Joan; Eyley, Samuel; El Kazzi, Salim; Rodríguez González, Miriam Candelaria; Pradhan, Bapi; Thielemans, Wim; Hofkens, Johan; De Feyter, Steven
Abstract : Controlled covalent functionalization of MoS2 by chemical reduction. Abstract : Covalent functionalization is one of the most efficient ways to tune the properties of layered materials in a highly controlled manner. However, molecular chemisorption on semiconducting transition metal dichalcogenides remains a delicate task due to the inertness of their surface. Here we perform covalent modification of bulk and single layer molybdenum disulfide (MoS2 ) using chemical activation of diazonium salts. A high level of control over the grafting density and yield on MoS2 basal plane can be achieved by this approach. Using scanning probe microscopies and X-ray photoelectron spectroscopy we prove the covalent functionalization of MoS2 .